Every note played [large type] : a novel - Genova, Lisa (Wheeler Publishing, a part of Gale, a Cengage Company, 2018)
"A once accomplished concert pianist, Richard now has ALS. As he becomes increasingly paralyzed and is no longer able to live on his own, Karina becomes his reluctant caretaker. As Richard's muscles, voice, and breath fade, both he and Karina try to reconcile their past before it's too late. This is a masterful exploration of redemption and what it means to find peace inside of forgiveness" -- Amazon.com.